Perlindungan Hukum Tenaga Kerja Wanita Ditinjau dari Hukum Nasional dan Hukum Internasional - Dhenia Sukmadianti; Bias Lintang Dialog; Budiman, Haris (Uniku Law Review, 2023)
The increasing number of migrant workers from year to year to work abroad is an indicator of globalization or international integrity. Sending Indonesian workers to other countries, has not been accompanied by a strong and comprehensive placement and protection system that can answer the problems of prospective Indonesian workers abroad. Both during pre-placement, placement, and after placement. The weak system of protecting Indonesian workers abroad, the large amount of violence that occurs against migrant workers, especially violence that occurs against female migrant workers. The legal protection given to migrant workers according to international law is contained in the International on the Protection of Human Rights of All Migrant Workers And Members of Their Family. This convention contains a series of standards to deal with the treatment of the welfare and rights of all migrant workers and members of their families, as well as contains obligations and responsibilities of countries regarding countries of origin, transit and places of work that benefit from international labor migration. In this case the state has a very important role to uphold the protection of migrant workers, especially women migrant workers. The method used in this study is a normative juridical approach using primary data and secondary data as data collection tools. The conclusion of this writing is that even though Indonesia already has regulations at the national and international levels, violence that occurs against migrant workers, especially women, still occurs a lot. Suggestions for the government are to make laws and regulations at the regional level and open up more employment opportunities, especially for women.   Meningkatnya jumlah pekerja migran dari tahun ke tahun, untuk bekerja di luar negeri merupakan salah satu indikator dari globalisasi atau integritas internasional. Pengiriman pekerja Indonesia ke negara lain, belum disertai dengan adanya sistem penempatan dan perlindungan yang kuat dan menyeluruh, yang dapat menjawab persoalan calon pekerja Indonesia di luar negeri. Baik selama pra penempatan, penempatan, dan purna penempatan. Lemah nya sistem perlindungan pekerja Indonesia di luar negeri, banyak nya kekerasan yang terjadi kepada pekerja migran, khususnya kekerasan yang terjadi pada pekerja migran wanita. Perlindungan hukum yang diberikan terhadap buruh migran menurut Hukum Internasional tertuang dalam International on The Protection of Human Rights of All Migran Workers And Member of Their Family. Konvensi ini berisi serangkaian standar untuk menangani perlakuan terhadap kesejahteraan dan hak-hak seluruh pekerja migran dan anggota keluarganya, serta berisi kewajiban dan tanggungjawab negara terkait negara asal, transit dan tempat mereka bekerja yang memperoleh keuntungan dari adanya migrasi pekerja Internasional. Dalam hal ini negara sangat berperan penting untuk menegakkan perlindungan terhadap pekerja migran, khususnya pekerja migran perempuan. Metode yang digunakan dalam penelitian ini adalah dengan pendekatan yuridis normatif dengan menggunakan data primer dan data sekunder sebagai alat pengumpul data. Simpulan dari penulisan ini meskipun indonesia sudah memiliki peraturan di tingkat Nasional maupun Internasional tetapi, kekerasan yang terjadi kepada pekerja migran khusus nya wanita masih banyak terjadi. Saran untuk pemerintah yaitu dengan membuav peraturan perundang undangan ditingkat daerah dan lebih banyak membuka lapangan pekerjaan khususnya untuk wanita.